E4. Remote prenatal follow-up of patients at risk for gestational hypertensive disorders: maternal and neonatal outcomes. (12th August 2016) - Lanssens, D.; Van Moerebeke, A.; van den Hoogen, A.; Geusens, N.; Grieten, L.; Gyselaers, W.
Abstract: Background : Gestational hypertensive disorders (GHD) are major contributors to maternal mortality worldwide. In Ziekenhuis Oost- Limburg (Genk, Belgium), a remote monitoring (RM) program for pregnant women at risk for developing GHD was initiated in January 2015 to evaluate the relevance of a RM program. RM is a relatively new approach that broadly can be defined as the application of telecommunication technologies in interchanging medical data, information and services between healthcare providers and patients. Aim : Evaluation of the role of RM in the obstetrical care for pregnant women at risk for GHD. Methods : A retrospective study was conducted in 44 pregnant women who developed GHD and had a RM prenatal follow-up. They sent twice daily blood pressure measurements and once daily weight measurements to our Clinical Call Center. Those patients were compared with 98 patients with confirmed GHD in routine care (RC). The inclusion period started at the first of January 2015 and ended 31 December 2015. All the interchanged data were analyzed in detail. Primary endpoints were: number of prenatal consultations and Maternal Intensive Care (MIC) admissions. Secondary endpoints were: maternal and neonatal outcomes. SPSS was used for statistical analysis. Results : There is no difference between the two groups in maternal demographics, gestational age at the first prenatal visit, the total number of prenatal visits, CTG's and echo's during pregnancy, or amount of days admitted to the MIC. In RM versus RC, the total number of MIC admissions (29% versus 74%; p < 0.01) and the number of long-stay birthing admissions to the MIC (18% versus 64%; p < 0.01) were lower. Maternal and neonatal outcomes were not different for gestational age at delivery, birthweight, birthweight percentile, length, Apgar at 1 min or at 5 min and pH arterial or venous. In RM versus RC, the number of spontaneous deliveries is higher (47% versus 27%; p = 0.01) and the number of admissions to the NIC was lower (11.3% versus 29.2%; p = 0.02). Discussion : A lower number of NIC and MIC admissions in RM versus RC were observed in this retrospective study. When confirmed in a prospective setup, cost effectiveness of prenatal RM can be evaluated.